Inoculation of Bacillus sphaericus UPMB-10 to young oil palm and measurement of its uptake of fixed nitrogen using the 15N isotope dilution technique - Ab. Aziz, Zakry Fitri; Shamsuddin, Zulkifli; Abdul Rahim, Khairuddin; Zakaria, Zin Zawawi; Abdul Rahim, Anuar (Japanese Society of Microbial Ecology / The Japanese Society of Soil Microbiology / Taiwan Society of Microbial Ecology / Japanese Society of Plant and Microbe Interactions, 2012)
There are increasing applications of diazotrophic rhizobacteria in the sustainable agriculture system. A field experiment on young immature oil palm was conducted to quantify the uptake of N derived from N2 fixation by the diazotroph Bacillus sphaericus strain UPMB-10, using the 15N isotope dilution method. Eight months after 15N application, young immature oil palms that received 67% of standard N fertilizer application together with B. sphaericus inoculation had significantly lower 15N enrichment than uninoculated palms that received similar N fertilizers. The dilution of labeled N served as a marker for the occurrence of biological N2 fixation. The proportion of N uptake that was derived from the atmosphere was estimated as 63% on the whole plant basis. The inoculation process increased the N and dry matter yields of the palm leaflets and rachis significantly. Field planting of young, immature oil palm in soil inoculated with B. sphaericus UPMB-10 might mitigate inorganic fertilizer-N application through supplementation by biological nitrogen fixation. This could be a new and important source of nitrogen biofertilizer in the early phase of oil palm cultivation in the field.